Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Channel Geometry on the Discrimination of Mechanically Impaired Red Blood Cells in Passive Microfluidics

Abstract: Abstract:In this work, we aimed at the discrimination of mechanically impaired red blood cells (RBCs) using passive microfluidic approaches. We investigated the impact of the channel geometry on the behavior of healthy RBCs (hRBCs) and thermally rigidified RBCs (T-rRBCs) flowing in (i) a Unique and Long Constriction (ULC) and (ii) a series of Oscillating Width Constrictions (OWC). To confront the two geometries, we evaluated potential biomarkers for cell discrimination such as their speed V, deformation index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Pipetting results in shear of RBCs, which leads to the formation and fixation of flow shapes like knizocytes (also referred to as trilobes) (Lanotte et al, 2016), known to form at high shear rates (Figure 5). This highlights that the speed of fixation is extremely fast, knowing that RBCs in flow relax to the static shape in between 100 ms (Amirouche et al, 2017) and 1 s (Braunmüller et al, 2011). We observed knizocytes when fixing with 1% glutaraldehyde, but not when fixing with lower concentrations, hinting to a slower fixation for lower concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…Pipetting results in shear of RBCs, which leads to the formation and fixation of flow shapes like knizocytes (also referred to as trilobes) (Lanotte et al, 2016), known to form at high shear rates (Figure 5). This highlights that the speed of fixation is extremely fast, knowing that RBCs in flow relax to the static shape in between 100 ms (Amirouche et al, 2017) and 1 s (Braunmüller et al, 2011). We observed knizocytes when fixing with 1% glutaraldehyde, but not when fixing with lower concentrations, hinting to a slower fixation for lower concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…This assumption would explain why at low hydrodynamic stress -where the cell properties dominate the recovery process and where the hydrodynamics can be neglected -we can assume being in an almost static configuration, the recovery time tend toward relaxation time values. In a previous study, we reported that at fixed hydrodynamic stress, shape recovery times of RBCs can be used to discriminate between healthy and mechanically impaired RBCs (Amirouche et al, 2017). In the present paper, we aim at demonstrating that our approach is sensitive enough to discriminate between different membrane modifications.…”
Section: Typical Behavior Of Healthy Rbcsmentioning
confidence: 80%
“…Mathematical models of deformable RBC with Discrete Element Methods have also been taken into account, along with the lattice Boltzmann models of immersed boundaries [172,173]. Other relevant studies include the assessment of shear dependencies in RBC adhesion [174], analysis of the changes in RBC stiffness [175], mechanical characterization of stored RBCs via mathematical models [176], donor-dependent aging curves based on microfluidic RBC models [177], effects of channel geometry in RBC sorting [178], and the assessment of RBC deformity using iron-dextran tests [179].…”
Section: Deformation Of Single Erythrocytes In Microchannelsmentioning
confidence: 99%